Mediating Effect of Students’ Motivation Between the Relationship of Classroom Environment and Mathematics Problem-Solving Skills - April Rose A. Soriamo; Sharie Rose C. Truya; Naomi Jhenne T. Epe; Baby Jean Richa; Abel E. Sadji (Goodwood Publishing, 2026)
Purpose: The main purpose of This study aimed to investigate the mediating effect of students’ motivation on the relationship between classroom environment and mathematics problem-solving skills among first-year Bachelor of Secondary Education major in Mathematics students at Davao del Norte State College. Research Methodology: Using a quantitative descriptive-correlational research design, data were collected from 79 randomly selected students through standardized questionnaires. Results: The study found significant positive correlations between classroom environment and students’ motivation, classroom environment and mathematics problem-solving skills, and students’ motivation and mathematics problem-solving skills. Regression analysis further confirmed that the classroom environment significantly influenced both students' motivation and mathematics problem-solving skills, while students' motivation also significantly influenced their mathematics problem-solving skills. However, the indirect effect of the classroom environment on mathematics problem-solving skills through students' motivation was not statistically significant, indicating that students' motivation does not mediate this relationship. This suggests that while motivation is an important factor, it does not serve as the mechanism through which the classroom environment affects problem-solving skills. Conclusions: Students’ motivation does not mediate the relationship between classroom environment and mathematics problem-solving skills. Limitations: The sample was limited to first-year mathematics students from a single institution, which restricted the generalizability of the findings to other contexts. Contributions: This study aims to generate insights that can strengthen students' preparedness for mathematical challenges in higher education.